2014
DOI: 10.1007/s12288-014-0450-9
|View full text |Cite
|
Sign up to set email alerts
|

Hodgkin Lymphoma Masquerading as Tuberculosis in a Young Chronic Smoker

Abstract: Hodgkin lymphomas are malignant hemato-lymphoid neoplasms involving lymph nodes and extra-nodal sites. Bone marrow infiltration at diagnosis is uncommon, occurring in approximately 10 % cases. Such infiltration, when present, is usually focal and often associated with extensive disease, systemic symptoms, cytopenias and unfavorable histology. In the unusual event of the absence of significant peripheral lymphadenopathy, these lymphoma-related B-symptoms may easily masquerade as an infectious illness. A 30-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In front of lymph node or vertebral involvement suggestive of TB, when the anatomopathological examination shows only a granulomatous lesion without caseous necrosis and negative acid-fast staining, the clinician should evoke a diagnosis of lymphoma. A study reported the case of a 30year-old man, a chronic smoker who was initially treated for a presumptive impression of TB for 6 months without improvement [8]. At the initial diagnosis, there was hilar lymphadenopathy and a few very small (<0.5 cm) abdominal and axillary lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…In front of lymph node or vertebral involvement suggestive of TB, when the anatomopathological examination shows only a granulomatous lesion without caseous necrosis and negative acid-fast staining, the clinician should evoke a diagnosis of lymphoma. A study reported the case of a 30year-old man, a chronic smoker who was initially treated for a presumptive impression of TB for 6 months without improvement [8]. At the initial diagnosis, there was hilar lymphadenopathy and a few very small (<0.5 cm) abdominal and axillary lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…As clinical presentation of lymphoma and tuberculosis are the same, definitive diagnosis is a challenging process (6). Immunohistochemical workup is required in most instances as the morphology may be altered by the ongoing other pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the reduction in the incidence of PTB worldwide, there has been no decrease in the frequency of LNTB. Lymphadenopathy, fever, weakness, night sweats, and weight loss are the most common clinical presentations of LNTB, causing a notable risk of confusing LNTB with lymphomas ( 12 , 13 ). Diagnostic imaging also presents challenges in the diagnosis of LNTB, as symptoms of LNTB may mimic those of other diseases such as neoplasms or sarcoidosis ( 6 ).…”
Section: Discussionmentioning
confidence: 99%